Poetics of Postmodernism and the Market - Gaižutis, Algirdas (Sociologija. Mintis ir veiksmas, 1998)
The article discusses the postmodern art on a few levels: first, its relationship with the vanguard and the mass culture, second, its eclectic existence and, third, the state of Lithuanian postmodernism. The author suggests that the earlier stylistic conventions and the rules no longer define the art. Rather, the inspiration is to be searched for not in the forms of human existence, but in the market itself.